The Effectiveness of Blockchain Technology Implementation by Notaries in Increasing the Security and Validity of Digital Investment Agreement Deeds - Titin Hartati; Riswadi Riswadi (Greenation Research & Yayasan Global Resarch National, 2025)
The development of blockchain technology has opened up significant opportunities in the legal world, including in the notarial realm, particularly in the creation of digital investment agreement deeds. This study aims to analyze the effectiveness of blockchain technology implementation by notaries in improving the security and validity of digital investment agreement deeds by reviewing relevant legal, institutional, and technological aspects. Blockchain is considered capable of providing an immutable, transparent, and secure digital recording system, thereby strengthening trust between parties and preventing deed forgery. However, the application of this technology in notarial practice in Indonesia still faces significant challenges, primarily due to the lack of regulations specifically governing the legality of blockchain-based notarial deeds. This study uses a normative juridical approach with an analysis of Law Number 2 of 2014 concerning the Office of Notaries, Law Number 1 of 2024 concerning Electronic Information and Transactions, and other relevant regulations. The results of the study indicate that despite its technological potential, the implementation of blockchain in notarial practice is still hampered by legal, infrastructure, and human resource constraints. Progressive legal reforms and public policy initiatives are needed to accommodate these digital innovations within the national legal system, as well as to encourage the digitalization of notarial services that are secure, accountable, and legally valid.